2010
DOI: 10.1590/s1677-04202010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Chill-induced changes in fatty acid composition of tonoplast vesicles from hypocotyls of Vigna unguiculata (L.) Walp.

Abstract: The present study was undertaken to investigate the changes induced by chilling on fatty acid composition of tonoplast vesicles from hypocotyls of Vigna unguiculata (L.) Walp. The 7 day-old control seedlings were grown at 25°C while treated seedlings were submitted to low temperatures (10°C and 4°C) for 4 days after 3 days germination. The chilling stress resulted in a differential inhibition of plant growth at 10°C and 4°C. Following chilling at 10°C and 4°C, the rate of unsaturated to saturated fatty acids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
2
4
1
1
Order By: Relevance
“…However, in 38°C condition, we observed low electrolytic leakage, consistent with the decrease in linolenic and linoleic. Rydlová et al (2011), also observed similar results in the association of flex plants with plant growth promoting Glomus species, while Oliveira et al (2010) found same results under chilling stress. Similar results have been observed in other species (Murakami et al 2000;Grover et al 2000;Guerzoni et al 2001;Falcone et al 2004).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, in 38°C condition, we observed low electrolytic leakage, consistent with the decrease in linolenic and linoleic. Rydlová et al (2011), also observed similar results in the association of flex plants with plant growth promoting Glomus species, while Oliveira et al (2010) found same results under chilling stress. Similar results have been observed in other species (Murakami et al 2000;Grover et al 2000;Guerzoni et al 2001;Falcone et al 2004).…”
Section: Discussionsupporting
confidence: 58%
“…Lipids are considered the main chemical component of biological membranes, which plays an important role in cellular permeability, fluidity, and membrane-bound enzyme activities. The structural and functional stability of membrane is essential for plant resistance to temperature stresses, whilst damage in membrane structure can affect the permeability and membrane-localized enzymes Ruelland and Zachowski 2010;Oliveira et al 2010). Lipid peroxidation serves as an indicator for oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect was observed in V. radiata (L.) Wilczek and Vigna unguiculata (L.) Walp. seedlings (Posmyk and Janas, 2007;Oliveira et al, 2010). However, in our study, this effect was reversible after 2 days of re-warming, especially in H-MEL roots, where H-MEL treatment caused a 20% increase in root length relative to C treatment (Table 1).…”
Section: Resultscontrasting
confidence: 49%
“…These scavengers stabilizes subcellular structures and buffers cellular redox potential under stress conditions (Wahid et al 2007;Zinn et al 2010), while their activity depends on the level of stress perception by plants. The structural and functional stability of membrane is essential for plant's resistance to temperature stress, while damage in membrane structure can affect the permeability and the activity of membrane-localized enzymes Ruelland and Zachowski 2010;Oliveira et al 2010). Since membrane bounded lipid hydroperoxides are difficult to measure due to their instability, we often rely on the degree of lipid peroxidation by quantifying the secondary breakdown products like MDA.…”
Section: Introductionmentioning
confidence: 99%